2022
DOI: 10.1108/xjm-08-2021-0213
|View full text |Cite
|
Sign up to set email alerts
|

Does commitment to environment and society pays? Evidence from COVID-19 impact on stock volatility

Abstract: Purpose This study aims to analyse whether investment in green and sustainable stocks provide some cushion during current precarious time. To compare the impact of COVID-19 on the volatility of sustainable and market-capitalisation-based stocks, daily returns from Greenex, Carbonex, Large-Cap, Mid-Cap and Small-Cap index have been analysed over a period of six years from 2015 to 2021. Design/methodology/approach At the outset, logarithmic return of all selected indices has been tested for possible unit root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Because the characteristic of stock market, if the company want to get high CAR, the company need to Focus more on early publicity and the user experience of the game itself. At the same time, the size and content of the new game information flaw should be strictly selected, it refers to the public test period price, public test number, channel selection and many other aspects [12].…”
Section: Discussionmentioning
confidence: 99%
“…Because the characteristic of stock market, if the company want to get high CAR, the company need to Focus more on early publicity and the user experience of the game itself. At the same time, the size and content of the new game information flaw should be strictly selected, it refers to the public test period price, public test number, channel selection and many other aspects [12].…”
Section: Discussionmentioning
confidence: 99%
“…They suggested the methodology offers a fresh method for gathering pertinent data from online user behavior to create practical predictors for predicting stock return volatility. A study on the impact of COVID-19 on stock volatility by Sharma et al (2022) found that COVID-19 has the greatest significant impact on the volatility of the large-cap index, according to the asymmetric power ARCH model, whereas COVID-19 has the greatest significant impact on the volatility of the mid-cap index, according to the exponential GARCH model. The recent study by Huang (2022) reported, the time series analysis approach is used to confirm the benefits and drawbacks of the prior model by comparing the historical value of the stock open price with the fitting value in addition to a number of other basic preparations for building the best model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The idea of "socially responsible investing (SRI)," or investment based on ESG criteria, has gained widespread acceptance over the past ten years. Sustainable stocks are becoming increasingly popular as an alternative to traditional profit-maximizing equities due to their emphasis on pursuing societal goals, including environmental conservation, social equity, and economic advancement (Sharma et al, 2022). Companies are contributing to United Nation's sustainable development goals (SDG's) through these practices.…”
Section: Introductionmentioning
confidence: 99%